Efforts to Prevent Child Age Marriage in The Study of Islamic Legal Philosophy and Indonesia Positive Law - Amberi, Mariani (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Children are the next generation of the nation who are expected to become ideal human beings, tough, superior, competitive and responsive to changing times, as well as being able to become a driving force for community and nation development to break down weakness, poverty and underdevelopment. The quality of Indonesian children greatly determines the existence and ability of the Indonesian nation to compete with other countries. This study uses the library research method (normative law) with an approach to law and philosophy of Islamic law. The data analyzed are legal rules contained in Islamic law and positive law. The research concluded that the fulfillment of children's rights is highly dependent on the government, society, the business world, and the media being present to be able to provide comprehensive protection. However, this will not be achieved because child marriage in Indonesia is still quite high. In global discourse, child marriage is considered a tradition that harms and protects human rights. The main negative consequences for girls are reduced risks of educational opportunities, reproductive health and increased risks of maternal and child mortality. Child marriage is also a source of psychological trauma and domestic and sexual violence. The results of this study indicate that the government has made efforts to reduce the number of child marriages with various regulations and policies, although they are considered not optimal, partly because there are no sanctions for perpetrators of child marriage. But there are still many who argue because in Islamic family law it is permissible to marry after puberty. Therefore, this article argues that form perspective of the philosophy of Islamic law, child marriage causes more harm, therefore prevention efforts must be supported by various elements, goverments, family, legal actor and society.